The use of Storytelling Methods to Develop Language Skills in Early Childhood Aged 5-6 Years: A case Study at Aisyiyah Bustanul Athfal Kindergarten in Makassar - Nurlina Jalil; Muh Nur Fuadi; Wahidah Wahidah; Fatmah Fatmah; Salmiati Salmiati; Andi Abd Muis; Siti Salina Binti Samaun; Numan Hayimasae; Manavavee Mamah (IJECA (International Journal of Education and Curriculum Application), 2026)
Research into the use of storytelling methods to develop language skills was conducted using the classroom action research method, with the aim of determining the outcomes of language skill development in pupils through the application of storytelling. The research involved 19 pupils and was carried out over two cycles and four stages: planning, action, observation and reflection. Data collection was carried out through planning, action, observation and reflection by applying several indicators of success in language skills, including listening, understanding the content of the story, vocabulary, confidence in speaking, and the ability to retell the story after the learning process had taken place. Quantitative descriptive data analysis was applied by calculating the percentage of children’s language skill achievement in each cycle. The research findings indicate that children’s language skills in Cycle I of the learning process, with the ‘developing very well’ success indicator, stood at 72.59%, and improved in Cycle II to 87.06% in the ‘developing very well’ category. A summary of the results from Cycle I and Cycle II indicates that the children’s language skills have exceeded the success criteria set as the benchmark for measuring the level of development of children’s language skills, which stands at 85%. Consequently, research employing the storytelling method is effective in developing pupils’ language skills, and can generate engaging, active and consistent learning experiences for the development of pupils’ abilities.